Análisis de los estados financieros mediante la aplicación de los indicadores financieros a la finca "Juana Fernández" del periodo 2019-2020. - Caamaño Guaman, Thalia Mishell; Villamao Carrillo, Ericka Estefania (Universidad Técnica de Machala, 2022)
The present titling work called ANALYSIS OF THE FINANCIAL STATEMENTS THROUGH THE APPLICATION OF THE FINANCIAL INDICATORS TO THE FARM "JUANA FERNÁNDEZ" FOR THE PERIOD 2019-2020, was carried out under the characteristic of case analysis, in this sense, the problem raised is It refers to the ignorance that has existed in the administration that lies in the financial indicators to determine where there are shortcomings, deviations of the Company, making it difficult to make timely decisions that allow the owner to analyze the information and have favorable strategies for your organization. For which a financial analysis and interpretations of the application of indicators were carried out in order to determine the performance of the Farm and determine how the administration of resources is developed, and if the procedures applied to date are proving profitable for the Farm. Performing a financial analysis is very important for different organizations because it helps to identify in more detail how your company is doing, its resources, its profits, internal procedures and techniques, and thus make decisions that allow their growth. Selecting the type of methodology that will be used within the present work leads to a detailed study of each of the types of approaches and existing paradigms, reaching the conclusion that the following methodology will be used: Descriptive-explanatory research, the method deductive, transactional design, quantitative approach and through the application of a survey questionnaire to the accountant and Farm Manager for the correct execution of the case. For the execution and application of the indicators, the first point was to observe the analysis of the Financial Statements to proceed to apply the Indicators and obtain the results of each one for their respective interpretation, allowing to identify their level of Liquidity, indebtedness, activity and profitability. Graphically, the results obtained in each of the indicators were presented, and what each of the analyzed accounts consisted of was explained, which allowed reaching the conclusion that the Company has low liquidity to face its short-term obligations, but despite that, it can take actions to recover, in addition, the Farm has its own resources and avoids financing with third parties, and in terms of profitability, low percentages were obtained due to the high costs of sale and expenses , the same ones that deserve an efficient administration and control by the Farm, to obtain favorable results. In conclusion, it was possible to contribute to the owner of the farm by informing what were the results obtained in the application of financial indicators, with the respective recommendations for the correct decision-making based on these results, and in this way make the corresponding improvements.
El presente trabajo de titulación denominados ANÁLISIS DE LOS ESTADOS FINANCIEROS MEDIANTE LA APLICACIÓN DE LOS INDICADORES FINANCIEROS A LA FINCA “JUANA FERNÁNDEZ” DEL PERIODO 2019-2020, se lo realizó bajo la característica de análisis de caso, en este sentido, el problema planteado se refiere al desconocimiento que ha existido en la administración que radica en los indicadores financieros para determinar en donde se encuentra falencias, desvíos de la Empresa dificultando la toma de decisiones oportunas que permita a la propietaria analizar la información y tener estrategias propicias para su organización. Para lo cual se realizó un análisis financiero e interpretaciones de la aplicación de indicadores para poder determinar el desempeño de la Finca y determinar cómo se desarrolla la administración de los recursos, y si los procedimientos aplicados hasta la actualidad están resultando rentables para la Finca. Realizar un análisis financiero resulta muy importante para las distintas organizaciones porque contribuye a identificar de manera más detallada cómo se encuentra su empresa, sus recursos, sus utilidades, los procedimientos y técnicas internas y de esta forma tomar decisiones que permitan el crecimiento de las mismas. Seleccionar el tipo de metodología que se utilizará dentro del presente trabajo conlleva a un estudio minucioso de cada uno de los tipos de enfoques y paradigmas existentes, llegando a la conclusión de que se utilizará la siguiente metodología: Investigación descriptivo-explicativo, se utilizó el método deductivo, el diseño transaccional, enfoque cuantitativo y mediante la aplicación de un cuestionario de encuesta al contador y Gerente de la Finca para la ejecución correcta del caso. Para la ejecución y aplicación de los indicadores se procedió como primer punto a la observación de los análisis de los Estados Financieros para proceder a aplicar los Indicadores y obtener los resultados de cada uno para su respectiva interpretación, permitiendo identificar su nivel de Liquidez, endeudamiento, actividad y rentabilidad. De manera gráfica se presentaron los resultados obtenidos en cada uno de los indicadores, y se procedió a explicar en qué consistía cada una de las cuentas analizadas, lo que permitió llegar a la conclusión de que la Empresa tiene una liquidez baja para hacer frente a sus obligaciones a corto plazo, pero a pesar de eso puede realizar acciones para recuperarse, además la Finca cuenta con recursos propios y evita financiarse con terceros, y en lo referente a la rentabilidad se obtuvieron porcentajes bajos debido a que existió altos costos de venta y gastos, los mismos que ameritan de una administración y control eficiente por parte de la Finca, para obtener resultados favorables. En conclusión, se logró contribuir a la propietaria de la Finca informando cuales fueron los resultados obtenidos en la aplicación de los indicadores financieros, con las respectivas recomendaciones para la correcta toma de decisiones en base a esos resultados, y de esta forma realizar las mejoras correspondientes.
Keywords: ESTADOS FINANCIEROS; INDICADORES; RENTABILIDAD